2018
DOI: 10.1159/000493169
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Radiolabeled Prostate-Specific Membrane Antigen Positron Emission Tomography/Computed Tomography for Primary Lymph Node Staging in Newly Diagnosed Intermediate to High-Risk Prostate Cancer Patients: A Systematic Review and Meta-Analysis

Abstract: Introduction: We aimed to assess the diagnostic accuracy of radiolabeled prostate-specific membrane antigen positron emission tomography (PSMA PET) or positron emission tomography/computed tomography (PET/CT) for primary lymph node (LN) staging in newly diagnosed intermediate to high-risk prostate cancer (PCa) patients. Material and Methods: The MEDLINE, PubMed, EMBASE, and Cochrane Library database from the earliest available date of indexing through May 31, 2018, were searched for studies evaluating the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 35 publications
2
23
0
1
Order By: Relevance
“…Perera et al reported a sensitivity and specificity of 0.86 (95% CI, 0.37-0.98) and 0.86 (95% CI, 0.03-1.00), respectively, but merged data from both biochemical recurrence and initial staging patients (5). A second, more recent, metaanalysis performed only on the initial staging population closely mirrored our results, with estimated sensitivity and specificity of 0.71 (95% CI, 0.59-0.81) and 0.95 (95% CI, 0.87-0.99), respectively (15). von Eyben et al reported the sensitivity and specificity for initial staging alone-0.70 (95% CI, 0.53-0.83)-and pooled specificity was 0.84 (95% CI, 24-99) (4).…”
Section: Discussionsupporting
confidence: 70%
“…Perera et al reported a sensitivity and specificity of 0.86 (95% CI, 0.37-0.98) and 0.86 (95% CI, 0.03-1.00), respectively, but merged data from both biochemical recurrence and initial staging patients (5). A second, more recent, metaanalysis performed only on the initial staging population closely mirrored our results, with estimated sensitivity and specificity of 0.71 (95% CI, 0.59-0.81) and 0.95 (95% CI, 0.87-0.99), respectively (15). von Eyben et al reported the sensitivity and specificity for initial staging alone-0.70 (95% CI, 0.53-0.83)-and pooled specificity was 0.84 (95% CI, 24-99) (4).…”
Section: Discussionsupporting
confidence: 70%
“…PSMA PET has shown encouraging diagnostic properties in prostate cancer since the first clinical trial was published with Ga-68-PSMA-11 in 2012 [34]. Since then, the use of PSMA PET has been evaluated in numerous settings, including primary staging and biochemical recurrence, as shown in recent systematic reviews [8][9][10][11][12][13]. However, these recent systematic reviews only present a fraction of the knowledge of PSMA PET for primary lymph node staging.…”
Section: Discussionmentioning
confidence: 99%
“…A final search on August 16 also showed 123 references. The validity of the PubMed search string was verified by the identification of all references presented in the latest systematic reviews of 68Ga-PSMA PET/CT for primary staging with pathology as the reference [8][9][10][11]13]. All references were imported into EndNote X8 (Clarivate Analytics, Philadelphia, US) and were evaluated for inclusion in the review.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…The specificity of CT was significantly lower the PSMA-PET (11). Recently, in a six-study meta-analysis, the overall sensitivity and specificity for PSMA-PET/CT was 71 and 95%, respectively (12). Hence, PSMA-PET is the most encouraging imaging modality for the detection of disease in LNs.…”
Section: Search For Metastases In Localized and Locally Advanced Prosmentioning
confidence: 96%